Advancing Gamma Knife Radiosurgery with Artificial Intelligence: A New Era of Precision and Efficacy - Devani, Kavin K.; Konar, Subhas K.; Vazhayil, Vikas V.; Thimmarayappa, Arun; Sadashiva, Nishanth (Indian Journal of Neurosurgery, 2025)
The recent surge in artificial intelligence (AI) applications is revolutionizing the medical field by offering astute data analysis and decision-making advancements. AI, via its algorithmic techniques, improves its performance over time by analyzing the data continuously and learning, identifying, and implementing subtle changes in the data presented to it. Gamma Knife radiosurgery is a noninvasive technique that represents an advanced and refined approach within the realm of stereotactic radiosurgery, predominantly utilized for the management of several brain pathologies by facilitating the exact targeting of aberrant brain tissue through the deployment of highly focused beams of gamma radiation, ensuring unparalleled precision and efficacy in treatment. This article delves into the transformative impact of AI on Gamma Knife radiosurgery, examining its influence across imaging, treatment planning, and posttreatment evaluation.
Keywords: artificial intelligence; Gamma Knife radiosurgery; neurosurgery